Nutrients removal from landfill leachate using free water surface and subsurface flow in constructed wetland - Afifi Akhiar (School of Environmental Engineering, University Malaysia Perlis, 2012)
Leachate is one of the major problems in landfill since it contained high levels of organic and inorganic matters. As it was highly contaminated, leachate could not be discharged directly into the surface water bodies. Therefore, constructed wetlands are highly efficient and low-cost alternative treatment systems for treating leachate. The main purpose of this study was to to determine the nutrients (phosphate, nitrate and ammonia) removal from landfill leachate using combined subsurface and free water surface flow in constructed wetland between planted and control (without plant) system. Other purpose was to determine the nutrients removal in two different hydraulic loading rates (HLR) which were 0.55 m/s and 0.39 m/s. The percentage removal between subsurface (SS) and free water surface (FWS) in both planted and control system and the uptake of nutrients by plants, Limnocharis flava in subsurface (SS) and Eichhornia crassipes in free water surface (FWS) were also investigated. A laboratory-scale constructed wetland was set up for this study. Planted system showed better removal compared to control system. Lower HLR removes phosphate better while higher HLR removes nitrate and ammonia better. Subsurface tank had good removal of nutrients but at some points free water surface had better removal. A combination of both subsurface and free water surface has excellent nutrients removal in constructed wetland. Eichhornia crassipes had higher nutrients uptake than Limnocharis flava but both plants have proven to play an important role in treatment of leachate.